Science and Technology for the Community: Training and Examination of Toddler Development at PGTK Khalifah, Sleman-Yogyakarta - Yekti Satriyandari; Fathiyatur Rohmah (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
One of the problems experienced by children is impaired growth and development. Child growth is an important stage that must be monitored to suit his age. Monitoring of child growth and development has not been maximally carried out so that developmental disorders in children are often detected too late. Meanwhile, children's growth and development disorders can be detected early to minimize the wider negative impact. Early detection is a comprehensive screening effort to find growth and development deviations and to identify and recognize risk factors (physical, biomedical, and psychological). Detection of growth and development can be done by health workers, health cadres and teachers. Monitoring growth and development in children can be routinely carried out every posyandu visit or every semester for pre-school children. Therefore, this program was carried out at PGTK Khalifah, Sleman-Yogyakarta. So far, at PGTK Khalifah there has never been any training on monitoring the growth and development of children in schools. Based on the results of the situation analysis there are children with autistic disorders. Activities are carried out through preparation, implementation (DDST training and examination), and evaluation. The material presented was well received and the teacher immediately tried to practice KPSP on students. The results of this service are confirmed, the implementation of growth and development checks on students and 80% of teachers are able to carry outgrowth and development detection checks regularly every semester.